Pengaruh Pemberian Kefir Madu terhadap Profil Lipid Tikus Galur Sprague Dawley Sindroma Metabolik: The Effect of Honey Kefir on the Lipid Profile of Sprague Dawley Rats with Metabolic Syndrome - Ilmi, Ibnu Malkan Bakhrul; Hardiansyah, Angga; Luailiya, Nikmatul; Avrilian, Putri Aria; Marjan, Avliya Quratul; Sugiyanti, Dina; Hayati, Nur (Universitas Airlangga, 2024)
Background: Metabolic syndrome is characterized as a collection of metabolic changes in the body that occur concurrently, including central obesity, dyslipidemia, insulin resistance, and blood pressure instability that can be improved through functional food products. One of the functional food products who prevents metabolic syndrome is honey kefir. Objectives: Analyzing the effect of goat milk kefir with the addition of randu honey on lipid profiles, specifically levels of total cholesterol, triglyceride and Low Density Lipoprotein (LDL) levels in diabetic rats. Methods: This study uses design true experimental research with pre-post test with control group design on 42 male Sprague Dawley rats which were randomly divided into 6 groups, namely healthy control (KS), negative control (KN), quercetin positive group (K1), metformin group (K2), kefir group (P1), and preventive group (P2). Groups KN, K1, K2, P1, and P2 were induced with metabolic syndrome. Groups KN, K1, K2, P1, and P2 were induced with streptozotocin (STZ) of 40 mg/kg BW. Group P2 was given 1.8 ml/200 g BW honey kefir simultaneously during STZ induction and High Fat Diet (HFD). The treatment of each group was carried out for 21 days. Group P1 was given 1.8 ml/200 g BW honey kefir. Measurement of lipid levels used the Cholesterol Oxidase Para Amino Phenazone (CHOD-PAP) method for total cholesterol and LDL levels, and Gliseril Phospo Para Amino Phenazon (GPO-PAP) for triglyceride levels. The research data were analyzed using One Way ANOVA, and related data were further examined using Duncan's post hoc test. Results: After 21 days of intervention, P1 rats had cholesterol levels of 117.7±7.49 mg/dl; triglycerides 106.82±7.79 mg/dl; LDL 43.57±1.89 mg/dl. Total cholesterol, triglycerides and LDL levels of P1 mice were not significantly different from K1 and K2 (p-value>0.05). Conclusions: Honey kefir can improve the lipid profile of diabetic mice such as quercetin and metformin.